2018
DOI: 10.11591/ijece.v8i2.pp666-672
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Automatic Extraction of Canine Cataract Object with Dynamic Controlled Fuzzy C-Means based Quantization

Abstract: Canine cataract is developed with aging and can cause the blindness or surgical treatment if not treated timely. Since the pet owner do not have professional knowledge nor professional equipment, there is a growing need of providing pre-diagnosis software that can extract cataract-suspicious regions from simple photographs taken by cellular phones for the sake of preventive public health. In this paper, we propose a software that is highly successful for that purpose. The proposed software uses dynamic control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…To identify the target object from low contrasted ultrasonography, pixel clustering method is a viable alternative and has been proven to be effective in engineering and medical domains [18][19][20][21][22]. In this pixel-based approach, the automatic segmentation process is usually divided into two phases-brightness enhancement for noise reduction and quantization-based object formation.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the target object from low contrasted ultrasonography, pixel clustering method is a viable alternative and has been proven to be effective in engineering and medical domains [18][19][20][21][22]. In this pixel-based approach, the automatic segmentation process is usually divided into two phases-brightness enhancement for noise reduction and quantization-based object formation.…”
Section: Introductionmentioning
confidence: 99%
“…For n data vectors and c fuzzy clusters (c < n), FCM classifies the image into clusters having similar pixels in the feature space with iteratively minimizing the cost function dependent on the distance of the pixels to the cluster centers in the feature domain. With such flexibility, FCM has been successful in segmentation problems in many medical and engineering domains [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, FCM classifies the image into clusters with similar pixels in the feature space, iteratively minimizing the cost function defined by the distance between the pixel and the candidate cluster centers in the feature domain. With such flexibility, FCM has been successful in solving segmentation problems in many medical and engineering domains [16][17][18][19][20][21][22]. However, it still suffers from object disconnection problems during learning, and our retrospective analysis of it [14] concluded that we need a better image-enhancement policy to overcome the difficulty of a cyst forming during the FCM process.…”
Section: Introductionmentioning
confidence: 99%